The Effect of Emotional Intelligence, Adversity Intelligence, and Self-Confidence on Science Learning Outcomes of Junior High School Students in Tamalate District, Makassar City - Nikma Amin; Muhiddin Palennari; Muhammad Arsyad; Firdaus Daud; Halimah Husain (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the effect of emotional intelligence, adversity intelligence, and self-confidence on science learning outcomes of students at public junior high schools in Tamalate District, Makassar City. The research used an ex post facto design with a survey approach involving 294 eighth-grade students selected through purposive sampling. Data were collected using validated questionnaires and documentation of students’ science scores, then analyzed using descriptive statistics and multiple linear regression. The results show that emotional intelligence, adversity intelligence, and self-confidence are generally at a moderate level, although variations among students are evident. Science learning outcomes are also categorized as moderate, indicating that most students have met minimum competency standards but have not yet achieved optimal performance. Inferential analysis reveals that emotional intelligence, adversity intelligence, and self-confidence each have a positive and significant effect on science learning outcomes. However, simultaneously, these three variables show a more substantial collective influence, although their contribution remains relatively limited, suggesting the presence of other influencing factors outside the study. In conclusion, students’ psychological factors play an important role in determining science learning achievement. Therefore, learning strategies that integrate emotional regulation, resilience building, and self-confidence enhancement are needed to improve students’ academic performance in science.